Josephus, the emperors, and the city of Rome : from hostage to historian - Hollander, William den. (Ancient Judaism and Early Christianity, 2014)
In Josephus, the Emperors, and the City of Rome William den Hollander places under the microscope the Judaean historian's own account of the latter part of his life, following his first encounters with the Romans. Episodes of Josephus' life, such as his embassy to Rome prior to the outbreak of the 1st Judaean Revolt, his prophetic pronouncement of Vespasian's imminent rise to the imperial throne, and his time in the Roman prisoner-of-war camp, are subjected to rigorous analysis and evaluated against the broader ancient evidence by the application of a vivid historical imagination. Den Hollander also explores at great length the relationships formed by Josephus with the Flavian emperors and other individuals of note within the Roman army camp and, later, in the city of Rome. He builds solidly on recent trends in Josephan research that emphasize Josephus' distance from the corridors of power.